Intramolecular Diels-Alder reaction in ionic liquids: effect of ion-specific solvent friction - Tiwari, Shraeddha; Khupse, Nageshwar D.; Kumar, Anil (Journal of Organic Chemistry, 2008)
The present work aims at understanding the role of viscosity or solvent friction in ionic liquids for an intramolecular Diels-Alder (IMDA) reaction of (E)-1-phenyl-4-[2-(3-methyl-2-butenyloxy)benzylidene]-5-pyrazolone (1). The results have been analyzed on the basis of the current theoretical models, and their failure to account for the observed trends is discussed in terms of ``effective'' viscosity or microviscosity. The rates of the reaction decrease with the increasing viscosity of the ionic liquids. As evident from the anionic effect, the solute-solvent specific interactions play a role in governing the kinetics of the reaction. The lower viscosities of the bistrifluoromethanesulfonimide [NTf(2)](-) based ionic liquids as compared to those based on tetrafluoroborate [BF(4)](-) anion fail to result in a corresponding acceleration in the rates of the reaction. These contradictory results indicate that solvent microviscosity, rather than the bulk macroscopic viscosity, should be the criteria for selecting the ionic liquids as reaction media.